Automatic multispectral MRI segmentation of human hippocampal subfields: an evaluation of multicentric test–retest reproducibility - Chiappiniello, Andrea; Tarducci, Roberto; Muscio, Cristina; Bruzzone, Maria Grazia; Bozzali, Marco; Tiraboschi, Pietro; Nigri, Anna; Ambrosi, Claudia; Chipi, Elena; Ferraro, Stefania; Festari, Cristina; Gasparotti, Roberto; et al. (Brain Structure and Function, 2021)
Accurate and reproducible automated segmentation of human hippocampal subfields is of interest to study their roles in cognitive functions and disease processes. Multispectral structural MRI methods have been proposed to improve automated hippocampal subfield segmentation accuracy, but the reproducibility in a multicentric setting is, to date, not well characterized. Here, we assessed test–retest reproducibility of FreeSurfer 6.0 hippocampal subfield segmentations using multispectral MRI analysis pipelines (22 healthy subjects scanned twice, a week apart, at four 3T MRI sites). The harmonized MRI protocol included two 3D-T1, a 3D-FLAIR, and a high-resolution 2D-T2. After within-session T1 averaging, subfield volumes were segmented using three pipelines with different multispectral data: two longitudinal (“long_T1s” and “long_T1s_FLAIR”) and one cross-sectional (“long_T1s_FLAIR_crossT2”). Volume reproducibility was quantified in magnitude (reproducibility error—RE) and space (DICE coefficient). RE was lower in all hippocampal subfields, except for hippocampal fissure, using the longitudinal pipelines compared to long_T1s_FLAIR_crossT2 (average RE reduction of 0.4–3.6%). Similarly, the longitudinal pipelines showed a higher spatial reproducibility (1.1–7.8% of DICE improvement) in all hippocampal structures compared to long_T1s_FLAIR_crossT2. Moreover, long_T1s_FLAIR provided a small but significant RE improvement in comparison to long_T1s ( p = 0.015), whereas no significant DICE differences were found. In addition, structures with volumes larger than 200 mm 3 had better RE (1–2%) and DICE (0.7–0.95) than smaller structures. In summary, our study suggests that the most reproducible hippocampal subfield FreeSurfer segmentations are derived from a longitudinal pipeline using 3D-T1s and 3D-FLAIR. Adapting a longitudinal pipeline to include high-resolution 2D-T2 may lead to further improvements.